2020
DOI: 10.1101/2020.06.06.137844
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Excitatory effects of dentate gyrus mossy cells on granule cells and area CA3: an vitro and in vivo study in adult mice

Abstract: Glutamatergic dentate gyrus (DG) mossy cells (MCs) innervate the primary cell type, granule cells (GCs), and GABAergic neurons which inhibit GCs. Prior studies suggest that the net effect of MCs is mainly to inhibit GCs, leading one to question why direct excitation of GCs is often missed. We hypothesized that MCs do have excitatory effects, but each GC is only excited weakly, at least under most experimental conditions. To address this hypothesis, MC axons were stimulated optogenetically in slices. A brief op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 167 publications
(388 reference statements)
8
12
0
Order By: Relevance
“…Consistent with previous reports (Bernstein et al, 2020;Botterill et al, 2019), hilar GFP cell bodies near the injection site strongly colocalized with the glutamatergic marker GluR2/3 ( Figure S1). GFP axons in dorsal DG were primarily restricted to the IML ( Figure 1C1-C3).…”
Section: Coronal Sectionssupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous reports (Bernstein et al, 2020;Botterill et al, 2019), hilar GFP cell bodies near the injection site strongly colocalized with the glutamatergic marker GluR2/3 ( Figure S1). GFP axons in dorsal DG were primarily restricted to the IML ( Figure 1C1-C3).…”
Section: Coronal Sectionssupporting
confidence: 92%
“…In contrast, the MOPP cell and neurogliaform cells have an axon that is localized to the area around their somata and this includes both the OML and MML (Armstrong et al, 2011;Halasy and Somogyi, 1993). Notably, the Drd2-Cre mouse has been suggested to show expression of Cre not only in MCs but also some hippocampal GABAergic neurons (Puighermanal et al, 2015), but we have found this rare (Bernstein et al, 2020;Botterill et al, 2019). Nevertheless, in the present paper we used two markers of GABAergic neurons and asked if there was colocalization of viral expression of MCs with GABAergic neuron labeling.…”
Section: Dgmentioning
confidence: 58%
See 2 more Smart Citations
“…Viral expression in Drd2-Cre +/mice was characterized by large hilar mCherry + cells proximal to the injection site and a dense band of mCherry + labeling in the inner molecular layer (IML) throughout the septotemporal axis of the DG, consistent with the location of MCs and their major axon projection ( Figure 1C-D; Scharfman, 2016). The pattern of viral expression has been validated in previous work by our laboratory (Botterill et al, 2019;Bernstein et al, 2020) and confirmed by others (Danielson et al, 2017;Bui et al, 2018;Yeh et al, 2018;Azevedo et al, 2019;Oh et al, 2019).…”
Section: Viral Expressionsupporting
confidence: 80%